2018
DOI: 10.1002/ir.20274
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Theoretical Frameworks for Intersectional Research on Women in STEM

Abstract: Research on women in STEM often silences the voices of minoritized populations, such as women of color, in part because the most commonly used theoretical frameworks do not center or contextualize their experiences. This chapter highlights the importance of critical perspectives and methodologies such as intersectionality in research design. We conclude with implications for using critical approaches to disrupt the status quo and advance minoritized populations in STEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
18
0
1
Order By: Relevance
“…Although prior literature clearly documents the need for intersectional approaches in the study of women of color’s experiences (Collins, 2008; Crenshaw, 1991; hooks, 1990a; Noddings, 1992), particularly in STEM spaces (Gaston Gayles & Smith, 2018), much of the research on equity in STEM has focused on gender or race/ethnicity. Perhaps as a result of the focus on women in STEM and students of color in STEM separately, institutions have increasingly created student groups to support women in STEM or students of color in STEM.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior literature clearly documents the need for intersectional approaches in the study of women of color’s experiences (Collins, 2008; Crenshaw, 1991; hooks, 1990a; Noddings, 1992), particularly in STEM spaces (Gaston Gayles & Smith, 2018), much of the research on equity in STEM has focused on gender or race/ethnicity. Perhaps as a result of the focus on women in STEM and students of color in STEM separately, institutions have increasingly created student groups to support women in STEM or students of color in STEM.…”
Section: Discussionmentioning
confidence: 99%
“…The category ‘Asian’ is incredibly broad, masking a huge amount of diversity itself [ 34 ]; different scholars having very different experiences based on cultural background and history [ 35 ]. Adopting an intersectional perspective will almost certainly change our understanding of representation [ 36 ], with many axes of identity (e.g. economic background, religion, disability, sexual orientation, gender, etc) also impacting recruitment and retention [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intersectional hypothesis suggests the distinct status of intersectional groups within a social hierarchy . Reporting disparities between intersectional categorizations may identify practices and outcomes that require intervention. , Institutional disaggregate data often present a more holistic view of how students in intersectional groups experience cultural marginalization when navigating social tensions within STEM academic settings …”
Section: Review Of Literaturementioning
confidence: 99%
“…Related prior research has focused on gendered differences in chemistry achievement ,, and persistence in chemistry majors, while others have explored differences among ethnicities in STEM access and achievement at both the high school ,, and undergraduate levels. , Intersectional research has often examined women of color in STEM generally, physics/astronomy, and engineering, mostly in undergraduate, graduate, or vocational contexts. ,, Research has identified sources of cognitive challenges in learning AP Chemistry, including higher-level problem solving, connecting macroscopic observations to particulate models, and applying mental algorithms to novel or unfamiliar chemical phenomena. , However, this does not explain demographic differences in coursetaking and achievement. Intersectional research suggests disparate science participation and performance may be related to sociocultural issues such as structural institutional inequities, a culture of marginalization, and hierarchical stereotypes. ,, The intersectional hypothesis was applied in the present study to examine precollege student participation and performance in AP Chemistry, which is consequential in terms of college chemistry readiness and improving diversity in the STEM academic pipeline and workforce . This framework is represented in Figure .…”
Section: Review Of Literaturementioning
confidence: 99%